Developing a robust tephrochronological framework for Late Quaternary marine records in the Southern Adriatic Sea: new data from core station SA03-11. (15th June 2015) - Matthews, I.P.; Trincardi, F.; Lowe, J.J.; Bourne, A.J.; MacLeod, A.; Abbott, P.M.; Andersen, N.; Asioli, A.; Blockley, S.P.E.; Lane, C.S.; Oh, Y.A.; Satow, C.S.; et al.
Abstract: Tephra layers are assuming an increasingly important role in the dating and correlation of Late Quaternary marine sequences. Here we demonstrate their potential by reporting a new study of the sediment sequence of marine core SA03-11, recovered from the Southern Adriatic Sea, which spans the last c. 39 ka. A total of 28 discrete tephra layers are reported from this sequence, 10 of which are visible in the core and a further 18 are non-visible cryptotephra layers. These have been analysed using more than 1400 WDS-EPMA measurements of glass chemistry and results have been compared with published chemical measurements obtained from relevant proximal and distal sites which preserve eruptive material dating to within the same time interval. The data show that a high proportion of the layers originate from the Campi Flegrei volcanic field but more distinctive layers are sourced from Vesuvius, the Aeolian Islands and Vulcano, and these provide key marker horizons. The results show that the sequence extends in time to the Campanian Ignimbrite at the base, that a number of the layers have robust age estimates that permit a better constrained age–depth model to be constructed for the sequence, and that the potential exists for importing terrestrially-based age estimates into marine contexts, thereby circumventing problems of incorporating reservoir uncertainties associated with marine radiocarbon dates. The WDS-EPMA dataset generated here also provides important new data that constrain key Late Quaternary tephra layers in the central Mediterranean region. Highlights: 28 tephra layers dated between 0 and 39 ka have been identified. 18 tephras are detected as cryptotephra, highlighting the value of this approach. New tephra layers have been identified from the Campi Flegrei and Aeolian Islands. We construct an age model for the core using terrestrial 14 C and tephra information. The results indicate the Adriatic has a varying 14 C reservoir between 30 and 39 ka.